2017
DOI: 10.1530/erp-17-0028
|View full text |Cite
|
Sign up to set email alerts
|

Automated left heart chamber volumetric assessment using three-dimensional echocardiography in Chinese adolescents

Abstract: BackgroundSeveral studies have reported the accuracy and reproducibility of HeartModel for automated determination of three-dimensional echocardiography (3DE)-derived left heart volumes and left ventricular (LV) ejection fraction (LVEF) in adult patients. However, it remains unclear whether this automated adaptive analytics algorithm, derived from a ‘training’ population, can encompass adequate echo images in Chinese adolescents.ObjectivesThe aim of our study was to explore the accuracy of HeartModel in adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…HM can provide more accurate results than linear and 2D methods, ensuring the optimization of diagnoses . Although time has been not analyzed in this study, previous experienced confirmed that HM saves time …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…HM can provide more accurate results than linear and 2D methods, ensuring the optimization of diagnoses . Although time has been not analyzed in this study, previous experienced confirmed that HM saves time …”
Section: Discussionmentioning
confidence: 72%
“…13 Although time has been not analyzed in this study, previous experienced confirmed that HM saves time. 7,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 Therefore, HM 3DE may have a chance to bridge the gap between the available technology and clinical practice. In recent studies, HM 3DE has been used to evaluate left ventricular systolic function in multiple populations 6 , 13 , 14 and in patients with various heart diseases, 15 but there is no unified standard for the border parameter settings, and there are few studies on Asian populations. Therefore, this study is important and worthy of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many patients with common cardiovascular issues were excluded. Further studies 8,10,11 have…”
Section: Discrepancies In the Previous Hm Literaturementioning
confidence: 96%